PENGARUH MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI 1 BANJARBARU - Anggun Anggun; Ahmad Nazif (STAI AL FALAH Banjarbaru, 2019)
This study aims to determine the effect of learning by using a jigsaw cooperative learning model on student learning outcomes, and whether there are differences in learning outcomes between students who are treated using cooperative learning models and students who are not given treatment. This type of research uses a quasi-experimental research sample method amounting to 26 students in class VIII E for the Experiment class and also totaling 26 students for class VIII A in the control class. The sampling technique is nonprobability sampling which does not provide equal opportunity/opportunity for each population to be selected as a sample, the research instrument used is in the form of multiple-choice tests and questionnaires. The results showed that the cooperative learning model applied to the experimental class could significantly influence student learning outcomes in PAI learning. This is evident from the results of data analysis using t-test statistics obtained count = 2.94 and table = 0.05 (1.07). So that the table (2.94> 1.07). This means that the alternative hypothesis is accepted (Ho rejected). Based on questionnaire data processing, it is known that all sample students (80.70%) like the Jigsaw cooperative learning model because it is fun and can improve student learning outcomes. Keywords: learning activities, cooperative jigsaw type, learning outcomes